Produção in vitro de embriões bovinos com cisteamina - Silva, Daniela Scherer da (2006)
Advanced reproductive techniques use the 3 phase of in vitro production for bovine embryos, i.e. in vitro maturation (IVM), in vitro fertilization (IVF) and in vitro culture (IVC) as support for a variety of studies. This study assessed the effect of cysteamine, a thiol component, on the embryonic development during maturation, fertilization and in vitro culture. Bos taurus indicus Cumulus-oocyte complexes (COC) obtained from cow ovaries collected at a slaughterhouse were randomly distributed in four groups: controlgroup (without cysteamine, n=488), cysteamine in maturation (n=487), cysteamine in fertilization (n=489) and cysteamine in the culture medium (n=493). All COC were matured for 24h in TCM-199+0,01IUrFSH/mL+0,05mgLH/mL+10% fetal calf serum (FCS). In the cysteamine-maturation group, the TCM-199 medium was supplemented with 150μM cysteamine. The COC were matured at 38.5ºC with 5% of CO2 in air and humid atmosphere. The IVF (D0=fertilization day) was performed for 18-22h in Talp-Fert medium with heparin and PHE under the same conditions as IVM. The medium of the cysteamine-fertilization group was supplemented with 150μM cysteamine. For sperm capacitation, the semen was thawed, selected by percoll gradient and insemination was done with 2x106 spermatozoa/mL. Presumed zygotes from all groups were cultured in SOF + 5% FCS. In the cysteamine culture group the SOF medium was supplemented with 150μM cysteamine. Culture was maintained at 5%CO2, 5%O2, 90%N2 and saturated humidity for 8 days. Cleavage rates were 86, 89, 88 and 90 respectively, for control, maturation, fertilization and culture groups. Percentage of blastocyst on D7 were 29, 31, 38 e 35 and blastocyst hatched on D9 were 21, 23, 27 and 29, respectively. This study showed that adding cysteamine to the fertilization or culture medium improve the blastocyst production. Commercial OPU/IVP programs maybe benefit from the use of cysteamine.